2018
DOI: 10.5812/jjhs.83410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Stress on the Work Ability of Iranian Firefighters

Abstract: Background: Occupational stress is one of the factors affecting social life and is known as a serious threat to the workforce health in the world. Firefighters are subject to frequent occupational stress due to their working conditions and tasks. Objectives: The current study aimed at investigating the effect of occupational stress dimensions on the work ability index of firefighters in a petrochemical company in Iran. Methods: A total of 130 shift-working and day-working firefighters were selected from a petr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…It is obvious that Zahedan firefighters have significant differences in lifestyle and working conditions compared to Tehran firefighters. Also, according to the results of a study published by Hatami and Afshari [25], the average work ability index was 34.65, which was lower than the value in our study. Given that the selected firefighters in the Hatami and Afshari studies were operating in one of the petrochemical industries, they may have been influenced by some influential variables such as job stress or different weather conditions from the population studied in our study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…It is obvious that Zahedan firefighters have significant differences in lifestyle and working conditions compared to Tehran firefighters. Also, according to the results of a study published by Hatami and Afshari [25], the average work ability index was 34.65, which was lower than the value in our study. Given that the selected firefighters in the Hatami and Afshari studies were operating in one of the petrochemical industries, they may have been influenced by some influential variables such as job stress or different weather conditions from the population studied in our study.…”
Section: Discussioncontrasting
confidence: 94%
“…According to the results of this study, there was an inverse linear relationship between age and ability to work in fire stations. In other words, older people were less able to work, and this result is consistent with previous studies in this field [25][26][27]32]; while the findings of Akbari et al were inconsistent with our study. They concluded that there is a positive correlation between age and work ability index [18].…”
Section: Discussionsupporting
confidence: 69%
“…The results of the included studies were qualitatively analyzed (Tab. 1) [1,12,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. www.journals.viamedica.pl…”
Section: Data Extraction and Synthesismentioning
confidence: 99%